Estimation of heterosis and the ability to combine yield attributes and seed yield in Indian mustard (Brassica juncea) - SINGH, KUNWAR HARENDRA; SINGH, LAL; SINGH, GUMAN; RAM, BHAGIRATH; RAI, PRAMOD KUMAR; SINGH, VIJAY VEER (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during winter (rabi) season of 2021–22 and 2022–23 at ICAR-Indian Institute of Soybean Research, Indore, Madhya Pradesh to analyse Line × Tester to estimate the general combining ability (GCA) and specific combining ability (SCA) of 11 advanced inbred lines used as female parents and 5 as testers analysis. The study also aimed to assess parental heterosis among 55 F1 crosses in Indian mustard [Brassica juncea (L.) Czern & coss]. Both gene actions like non-additive and additive were having an impact, with non-additive gene actions predominating. Due to their extraordinarily substantial favorable GCA impacts on seed output and seed-related characteristics, lines RE 11, IC 597880, and CN105379 as well as testers M 37 and DRMRIJ 31, were chosen as the best general combiners. In terms of growth attributes i.e. plant height, length of main shoot alongwith yield attributes i.e. number of primary branches, test weight, oil content and other contributing traits, many hybrids also exhibited highly desirable SCA effects for different traits. The best hybrids determined by SCA effects also showed a strong correlation between heterosis and SCA effects for different traits. In addition to better parent heterosis and SCA effects, a relationship between parental combinations was observed on the basis of SCA effects. A close relationship between SCA effects and heterosis was also observed among best hybrids identified on the basis of SCA effects. Hybrid combinations EJ 22/ RC 273 (65.93%), IC 597875/RC 273 (51.80%), RNN 505/RC 273 (46.68%), Pusa Bahar/M 37 (42.36%), RNN 505/M 37 (40.76%), RE 11/M 37, Pusa Bahar/M 37, RNN 505/M 37, Pusa Bahar/RC 273, EJ 22/RC 273, CN 105379/ DRMRIJ 31, RNN 505/RC 273 and IC 597875/RC 273 exhibited highly significant and positive magnitude of SCA effects and better parent heterosis with higher per se performance for seed yield. After converting the parental lines into the proper CMS and fertility restorer lines, highly significant cross combinations may be used in the hybrid development programme.